Application of Food Truck Media as Fun Learning to Improve Writing Skills - Rosida, Sisi; Fitriani, Eka Surya; Losi, Rizky Vita (International Conference on Sciences Development and Technology, 2023)
The teaching assistance program requires literacy learning activities carried out by students collaboratively with lecturers and teachers. Students' lack of ability is due to monotonous and inactive learning procedures. This condition is seen from the students' lack of understanding in analyzing texts, resulting in difficulties in learning Indonesian which consists of six meetings per week. To overcome this problem, digital counseling was held for Indonesian language learning which aimed to maximize writing skills using Food Truck literacy media, as an interesting learning process. This research was located at Putra Anda Binjai Vocational School, where the Education Unit Teaching Assistance program activities were carried out. The methods used in this research are lectures, discussions and demonstrations. The research results show that counseling using Food Truck media can be used as an alternative in improving students' writing skills, this increases students' creativity in learning Indonesian. During the activity, students played an active role in the fun learning process using Food Truck media "very well". Student activity is implemented in understanding online ordering, work procedures, and practice of making sweet martabak as a fun learning experience between teachers and students